16.1k views
4 votes
Lily begins solving the equation 4(x – 1) – x = 3(x + 5) – 11. Her work is shown below.

4(x – 1) – x = 3(x + 5) – 11
4x – 4 – x = 3x + 15 – 11
3x – 4 = 3x + 4
How can her partial solution be interpreted?

The equation has one solution: x = 0.
The equation has one solution: x = 8.
The equation has no solution.
The equation has infinite solutions. help on a timer

User Khalil
by
4.6k points

2 Answers

4 votes

Answer:

Has no solution

Explanation:

User Necixy
by
5.1k points
4 votes

Answer:

The equation have no solution.

3x - 4 = 3x + 4

-4 = 4

The statement is false

User Kerkouch
by
4.5k points